The book of lost saints : [book club bag] - Older, Daniel Jose (Feiwel & Friends, 2022)
The spirit of Marisol, who vanished during the Cuban Revolution, visits her nephew, Ramon, in modern-day New Jersey, and her presence prompts him to investigate the story of his ancestor, unaware of the forces driving him on his search